2012
DOI: 10.1371/journal.pone.0045491
|View full text |Cite
|
Sign up to set email alerts
|

Immune Sculpting of Norepinephrine on MHC-I, B7-1, IDO and B7-H1 Expression and Regulation of Proliferation and Invasion in Pancreatic Carcinoma Cells

Abstract: BackgroundThe sympathetic neurotransmitter Norepinephrine (NE) contributes to tumorigenesis and cancer progression. This study aims to investigate the role of NE in modulating the immune phenotype and allowing pancreatic carcinoma (PC) cells to escape the immune response.MethodsVaried concentrations of NE and interferon-gamma (IFN-γ) were administrated to MIA PaCa-2 and BxPC-3 cell lines for 48 hours. Proliferation and invasion were then investigated using an MTT assay and a membrane invasion culture system re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
13
1
Order By: Relevance
“…B7-H1 has been previously shown to regulate cell migration and invasion in pancreatic carcinoma cells [27]. Our observations that B7-H1 expression played an important role in HCT116 cell proliferation and apoptosis led us to assess the function of B7-H1 on cell migration and invasion in colon cancer cells.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…B7-H1 has been previously shown to regulate cell migration and invasion in pancreatic carcinoma cells [27]. Our observations that B7-H1 expression played an important role in HCT116 cell proliferation and apoptosis led us to assess the function of B7-H1 on cell migration and invasion in colon cancer cells.…”
Section: Resultsmentioning
confidence: 93%
“…Though some research groups have confirmed that tumor cells expressing B7-H1 had a high proliferative index [14,27], most groups tended to believe B7-H1 prevent tumor destruction only by forming “a molecular shield [18,29]” but not forming “a more powerful spear” [18,30]. Our finding provides powerful evidence that B7-H1 may have oncogenic function during colonic carcinogenesis, which shed a new light on the function of B7-H1 in colorectal cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent reports have demonstrated that NE can act as a pro-survival signal to tumour cells leading to increased metastasis, growth and diminished therapeutic response 4954 . We hypothesized that mild sub-thermoneutral housing temperatures could elicit a sympathetic cold stress response that would increase levels of NE, which would activate pro-survival pathways in these tumours by binding to β-adrenergic receptors.…”
Section: Resultsmentioning
confidence: 99%
“…One study observed that pancreatic tumor cells exposed to NE had decreased expression of MHC class I molecules as well as the co-stimulatory ligand B7-1, and increased levels of immunosuppressive indolamine-2,3-oxygenase (IDO) and B7H-1 (PD-L1), the ligand for the programmed cell death receptor (PD-1). While these changes only persisted for a short period of time, these phenotypic changes on cancer cells would not only prevent T cell recognition, but also impair their function by depleting essential nutrients such as tryptophan (by IDO) and inducing exhaustion even in activated lymphocytes [91]. …”
Section: Stress and Therapeutic Responsesmentioning
confidence: 99%